Quantitative risk assessment of offshore carbon dioxide injection system considering seismic effects. (October 2018) - Lee, Younggeun; Lee, Gunhak; An, Jinjoo; Kim, Kyeongsu; Ahmed, Usama; Lee, Chul-Jin; Han, Chonghun
Highlights: Quantitative risk assessment is performed on topside CO2 injection system. Modified QRA methodology considering seismic effect is applied. Domino-effect and multi-hazard are considered by using Bayesian network. Risk mitigation and reduction are performed to manage the risks. Abstract: Quantitative risk analysis (QRA) is one of the most generally used safety analysis measures for risk management in process industries. Currently, earthquakes occur worldwide, resulting in significant damage. Despite the importance of considering the danger of earthquakes, however, seismic effects are often not included in risk analysis owing to difficulties in considering the multi-hazard nature and domino effects of earthquakes. In this study, an improved methodology for QRA was proposed to consider the seismic effects including domino effects, and multi-hazard impacts of an earthquake by using a Bayesian network (BN). This analysis was applied to a topside CO2 injection system for underground storage, which is susceptible to seismic effects. Because frequency analysis is based on a causal relationship, the BN can be used to simultaneously consider domino effects and multi-hazard risks. As a result, the societal risk integral, one of the factors in risk analysis, was 9.667 × 10 - 4 / y e a r in modified QRA; this value shows an increase of 3.9% compared with the societal risk integral in conventional QRA. Furthermore, the value can be increased to 35% in the sensitivity analysis depending on annual exceedance probability (AEP). This result shows the importance of considering seismic effects, including both the domino effect and multi-hazard impacts, in QRA. A risk reduction method was additionally applied to mitigate the process risk.